2010
DOI: 10.1007/s00253-009-2404-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of amylase from soil metagenomic library derived from Northwestern Himalayas

Abstract: The increasing demand for novel biocatalysts stimulates exploration of resources from soil. Metagenomics, a culture independent approach, represent a sheer unlimited resource for discovery of novel biocatalysts from uncultured microorganisms. In this study, a soil-derived metagenomic library containing 90,700 recombinants was constructed and screened for lipase, cellulase, protease and amylase activity. A gene (pAMY) of 909 bp encoding for amylase was found after the screening of 35,000 Escherichia coli clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…Firmicutes were best with approximately 70% and Actinobacteria worst with around 10%, suggesting that E. coli could be a suitable host for the ikaite library given the high fraction of Firmicutes , although the study did not consider other limiting factors. The library constructed had relatively few clones, but the hit-rate was comparable to those of similar studies: one α-amylase was found when screening a cosmid-library of 35,000 clones [38], six esterases were identified in a screening of 60,000 fosmid clones [8], 11 cellulases were found when screening a small insert BAC-library of 10,000 clones [39], three β-galactosidases in a screening of 2,100 plasmid clones [40], one amylolytic enzyme in a screening of 30,000 plasmid clones [41], one cellulase in a plasmid library of 8,500 clones [42], and 38 amylases, 13 phosphatases but no proteases in a screening of 32,000 plasmid clones [43]. …”
Section: Resultsmentioning
confidence: 64%
“…Firmicutes were best with approximately 70% and Actinobacteria worst with around 10%, suggesting that E. coli could be a suitable host for the ikaite library given the high fraction of Firmicutes , although the study did not consider other limiting factors. The library constructed had relatively few clones, but the hit-rate was comparable to those of similar studies: one α-amylase was found when screening a cosmid-library of 35,000 clones [38], six esterases were identified in a screening of 60,000 fosmid clones [8], 11 cellulases were found when screening a small insert BAC-library of 10,000 clones [39], three β-galactosidases in a screening of 2,100 plasmid clones [40], one amylolytic enzyme in a screening of 30,000 plasmid clones [41], one cellulase in a plasmid library of 8,500 clones [42], and 38 amylases, 13 phosphatases but no proteases in a screening of 32,000 plasmid clones [43]. …”
Section: Resultsmentioning
confidence: 64%
“…Amylases have been reported from a number of metagenomic libraries but only a few of them were characterized [23,24,31]. In the present study, the identification of a novel GH-57 family member from a deep-sea metagenomic library will contribute to a better understanding of a diversified glycogen biosynthesis in oceanic organisms.…”
Section: Discussionmentioning
confidence: 94%
“…Amylases were the first enzymes to be discovered and described5 and are among the most important enzymes used for biotechnological purposes, from food to paper industries6. Numerous studies were focused on the discovery of new amylases originating from cultured bacteria, and more recently from metagenomic DNA.…”
mentioning
confidence: 99%
“…Numerous studies were focused on the discovery of new amylases originating from cultured bacteria, and more recently from metagenomic DNA. These investigations allowed the detection of amylases with interesting characteristics, such as amylases active in various conditions such as low6 or high7 temperature, low8 or high9 pH. Amylases belong to glycoside hydrolases (GH-)10 and are clustered into several families, mainly GH-13, GH-14, GH-15 and GH-57711, based on similarities in primary and tertiary structures together with conservation of the catalytic residues.…”
mentioning
confidence: 99%